2014
DOI: 10.1080/07900627.2014.895926
|View full text |Cite
|
Sign up to set email alerts
|

Increasing access to water services: a cost-recoverable pricing model

Abstract: Pricing policies can serve as a low-cost and effective tool for increasing access to water and sanitation services among poor households while allowing the provider to recover costs. An empirical model is applied to contingent-valuation survey data for water services in Cebu, Philippines. Pricing policies that utilizes a low one-time connection fee and differentiates tariffs based on wealth results in a 3 to 9-fold increase in water services access by poor households over the base pricing policy. The results p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Barbosa and Brusca, 2015;Chun, 2014;Farolfi and Gallego-Ayala, 2014;Sibly and Tooth, 2014;Guerrini and Romano, 2013;Olmstead and Stavins, 2009;Letsoalo et al, 2007). From a policy perspective, the European Union Water Framework Directive promoted taxing water users in a way that reflects the scarcity value of water.…”
Section: Introductionmentioning
confidence: 99%
“…Barbosa and Brusca, 2015;Chun, 2014;Farolfi and Gallego-Ayala, 2014;Sibly and Tooth, 2014;Guerrini and Romano, 2013;Olmstead and Stavins, 2009;Letsoalo et al, 2007). From a policy perspective, the European Union Water Framework Directive promoted taxing water users in a way that reflects the scarcity value of water.…”
Section: Introductionmentioning
confidence: 99%
“…Water pricing is one of various economic policy instruments that could be used to increase the efficient and rational use of water . Numerous studies addressing urban water‐pricing topics have been conducted . A survey on water pricing models concluded that this economic instrument is effective in combining water and sanitation services’ efficiency and revenue requirements.…”
Section: Introductionmentioning
confidence: 99%
“…7 Numerous studies addressing urban water-pricing topics have been conducted. [8][9][10] A survey on water pricing models 11 concluded that this economic instrument is effective in combining water and sanitation services' efficiency and revenue requirements. Urban water pricing policies are a lowcost and effective tool to increase access to water and sanitation services.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations